(untitled) (Journal of Surgical Sciences, 2019)
Tissue that is damaged and poorly oxygenated as a result of swelling, trauma or inflammation has been shown to have a positive response to laser therapy irradiation. At present, cutaneous lesions represent a dilemma of global proportions and instigate great clinical interest because of the high morbidity associated with changes in the normal healing process. Among the clinical aspects involving this issue, we emphasize tissue repair time in an effort to make the process quicker and more harmonious, reduce possible complications in lesion resolution, and allow an adequate choice of therapy. Laser light energy is highly absorbed by skin and subcutaneous tissue and therefore penetration is key to therapeutic results. Among the methods currently available, low-level laser therapy (LLLT) stands out. Here we present a case of 78 years old lady with multiple variable non healing ulcers on back. Appropriate antibiotics and regular dressing failed to heal the lesions. So we have decided to apply low level laser therapy. At the end of 8th week the wound looked pretty healthy. No untoward reaction or side effect was reported by the patient. Journal of Surgical Sciences (2014) Vol. 18 (1) : 38-42